Case of Morvan syndrome with anti‐Ma2/Ta antibodies. Issue 4 (1st August 2016) - Nishioka, Kenya; Hoshino, Yasunobu; Kanai, Kauzuaki; Ueno, Shinichi; Nakazato, Tomoko; Takanashi, Masashi; Tanaka, Ryota; Yokoyama, Kazumasa; Arimura, Kimiyoshi; Kuwabara, Satoshi; Hattori, Nobutaka
Abstract: The anti‐paraneoplastic (Ma2/Ta) antibody is related to testicular, lung and ovarian cancers, and might cause paraneoplastic neurological disorders. We present a 25‐year‐old woman presenting various neurological symptoms of myokymia, chronic widespread pain, tremor, excessive daytime sleepiness, impaired eye of movements, and seizures and autonomic symptoms related to anti‐Ma2/Ta antibodies. Needle electromyography showed spontaneous multiplet and myokymic discharges in the left vestus lateralis. Thus, we diagnosed her as Morvan syndrome. After initiation of steroids, plasma exchange and dantrolene, her symptoms partially improved with decreasing intensity of the antigen of anti‐Ma2/Ta antibodies, from moderate strong to borderline. The present case expands the clinical spectrum of anti‐Ma2/Ta antibodies‐related disorders to include the existence of neuroimmune activation and Morvan syndrome. Abstract : We reported a case, 25 years old woman, Morvan syndrome who complicated with various neurological symptoms of myotonia, chronic pain, epilepsy, and ovarian tumor, with anti‐Ma2/Ta antibodies.